2008
DOI: 10.1080/09638280701265596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognostic factors for bladder function recovery of patients with spinal cord and cauda equina lesions

Abstract: Bladder recovery in patients with complete SCL is limited. ASIA B patients showed a better neurological recovery and, concurrently, better bladder function recovery than ASIA A patients, thus demonstrating the importance of sensation preservation for recovery. Younger patients show better bladder recovery than older ones, probably because of different efficiency of spinal cord plasticity. Finally, patients with good neurological recovery may not achieve volitional voiding. Patients with bladder function recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…By logistic regression, etiology was not a determinant of improved bladder control. AIS level at admission was the chief predictor of good bladder control at discharge; these findings are consistent with other studiesFScivoletto 25 found that patients with AIS D grade and, in particular, those with Brown-Sequard and central cord syndromes experience the greatest recovery in bladder function. The two populations had comparable discharge destination rates, with B80% of patients returning home.…”
Section: Discussionsupporting
confidence: 90%
“…By logistic regression, etiology was not a determinant of improved bladder control. AIS level at admission was the chief predictor of good bladder control at discharge; these findings are consistent with other studiesFScivoletto 25 found that patients with AIS D grade and, in particular, those with Brown-Sequard and central cord syndromes experience the greatest recovery in bladder function. The two populations had comparable discharge destination rates, with B80% of patients returning home.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the finding of PRV-labeled neurons descending in the crossed pathway provides neuroanatomical evidence for the bilateral reflex modulation of the spared bulbospinal connections following chronic spinal hemisection injury, and implicates their potential role in the rapid recovery of sexual and bladder function seen in animals with lateral hemisection injury Little et al, 1991;Pritchard et al, 2010). A lateral hemisection injury in humans, sometimes referred to as Brown-Séquard syndrome, also results in a good prognosis for pudendal function, with return to voluntary voiding and less occurrence of detrusor-sphincter dyssynergia (Scivoletto et al, 2008). As is true for locomotor ability after hemisection, only a percentage of the pathway fibers in the spared lateral funiculus appear to be necessary for functional recovery (Schucht et al, 2002), particularly if the spared pathway is strengthened through plasticity (Babu and Namasivayam, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Both Akkoc et al [12] and Moslavac et al [13] concluded that patients with SCI should be followed with the same care regardless of the type of SCI (complete or incomplete). In contrast, Scivoletto et al [14], after analyzing 269 patients with SCI con- cluded that patients ASIA B achieved better functionality than ASIA A.…”
Section: Discussion/conclusionmentioning
confidence: 89%